Policies and politics in Malaysian education education reforms, nationalism and neoliberalism - Joseph, Cynthia (Routledge critical studies in Asian education, 2018)
This book draws on elements of critical social theory, research on globalization, neo liberalism and education, and Malaysian Studies to understand the interplay of globalization, nationalism, cultural politics and ethnicized neoliberalism in shaping the educational reforms in Malaysia. The authors in this volume focus on the interplay of neoliberalism, nationalism, ethnic and cultural politics in shaping the educational reforms in Malaysia.